Socio-environmental risks of five rural communities in Napo province from the Ecuadorian Amazon - Abril, R. V.; Marín, Haidée; Salazar, Cindy; Amancha, Nelly; Alvarado, Sumac; Aguinda, Shirma; Bravo, C. A. (Cuban Journal of Agricultural Science, 2022)
The objective of this study was to identify the main socioenvironmental risks to which rural communities are exposed: Chontapunta, Ahuano, Ila, Chucapi and El Capricho, from Napo province, in Ecuador. A random survey was applied, as an information collection instrument, to determine the socioeconomic, houses, disaster memory and emergency preparedness characteristics. The results show that there are different ethnic groups, with a diverse level of education. The risks of pests in crops and human epidemics were detected, exceeding 40 % of those surveyed in the Ahuano, Chonta Punta and El Capricho communities. As for the communities, 25 % reported risks of natural origin, such as floods and earthquakes. The communities have piped water and the waste water is not treated. They have daily and weekly waste collection services, most of them have an educational center and, to a lesser extent, health centers and public spaces. In the risks close to the houses, there are more reports about the presence of nearby trees and rivers. The analysis of variance showed ethnic self-identification and time of residence as the factors that reported the highest number of variables with differences for P ≤ 0.05. It is concluded that the areas are exposed, mainly, to physical and biological risks. The emergency response capacity is not developed, in terms of infrastructure, preparation and equipment. Key words: anthropic, community, natural, preparation, risk.